(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
The article examines the role of theoretical pluralism in the study of International Relations through three major theoretical traditions: realism, liberalism and constructivism. Contemporary world politics is marked by the coexistence of conflict and cooperation, the persistence of power politics, the growing role of international institutions, and the increasing significance of norms, ideas and identities. In such conditions, no single theoretical approach can fully explain the complexity of international processes. Realism highlights the importance of power, security, national interest and the anarchic structure of the international system. Liberalism focuses on cooperation, international institutions, interdependence, law and democracy. Constructivism draws attention to norms, identity, ideas and the social construction of state interests. The article argues that theoretical pluralism should not be understood as a mechanical combination of different theories, but rather as a conscious and methodologically grounded use of different analytical lenses depending on the research problem, the object of analysis and the nature of the international process under study.